Real-time biofeedback is more effective than sham feedback for modifying high risk biomechanics - Bonnette, Scott (J Sport Rehabil, 2019)
CONTEXT: Existing anterior cruciate ligament (ACL) injury prevention programs have failed to reverse the high rate of ACL injuries in adolescent female athletes. OBJECTIVE: This investigation attempts to overcome factors that limit efficacy with existing injury prevention programs through the use of a novel, objective, and real-time interactive visual feedback system designed to reduce the biomechanical risk factors associated with ACL injuries. DESIGN: Crossover study. SETTING: Medical center laboratory. PARTICIPANTS: Twenty female participants (age = 19.7 ± 1.34 y; height = 1.74 ± 0.09 m; weight = 72.16 ± 12.45 kg). METHODS: Participants performed sets of 10 bodyweight squats in each of eight training blocks (i.e., four real-time and four control blocks) and three testing blocks for a total of 110 squats. Feedback conditions were blocked and counterbalanced with half of participants randomly assigned to receive the real-time feedback block first and half receiving the control (sham) feedback first. RESULTS: Heat map analysis revealed that during interaction with the real-time feedback, squat performance measured in terms of key biomechanical parameters was improved compared to when participants squatted with the sham stimulus. CONCLUSION: This study demonstrates that the interactive feedback system guided participants to significantly improve movement biomechanics during performance of a body weight squat, which is a fundamental exercise for a longer-term ACL injury risk reduction intervention. A longer training and testing period is necessary to investigate the efficacy of this feedback approach to effect long-term adaptations in the biomechanical risk profile of athletes.